«Risponde Giulietta Masina»: discorso sessuale, corpo attoriale, contesto mediale attraverso la rubrica di posta (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
The essay sets out to explore the intersections and connections between cinematographic and sexual discourse starting from a specific point of observation: Giulietta Masina’s readers’ mail column in “La Stampa” from 1968 to 1976.The corpus of letters to the actor is studied in three directions: the first focuses on the senders and intends to reconstruct the typologies, priorities and interests of the (male and female) writers; the second looks at the recipient and asks about the relationship between the epistolary corpus and the actor’s star personality (compound result of the transformation of her public image between the Fifties and Sixties marked by autobiographical characteristics and persistent references to her role as Fellini’s wife); the final aim of this case study is to draw more general cues on the sex storytelling strategies used by the cinema in a particular phase of Italy’s history.
Keywords: Italian cinema; Giulietta Masina; female star fan; sex storytelling